ANALISIS BUDAYA KERJA PADA PUSAT PENDIDIKAN INTELIJEN KEAMANAN LEMBAGA PENDIDIKAN DAN PELATIHAN POLRI SOREANG BANDUNG - Diani Indah; Purwanto Purwanto (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2020)
The Security Intelligence Education Center of the Education and Training Institute of the Indonesian National Police (Pusdik Intelkam Lemdiklat Polri) is a part of the Indonesian National Police organization which has the main task of preparing human resources of the Indonesian National Police in the intelligence field. In building professional, modern, and trusted human resources, Pusdik Intelkam continues to strive to improve the quality of human resources in its internal organizations through strengthening work culture.This study aims to examine the work culture in the Pusdiklat Lemdiklat Polri Soreang Bandung. The method used is qualitative with a descriptive approach. Data obtained through interviews, observations, and documentation studies. The results showed that the work culture in the Pusdiklat Lemdiklat Polri Soreang Bandung had run quite well, but not yet optimal. In general, the main tasks and functions were carried out well, the rules of discipline had been socialized, as well as the value of leadership had been instilled through delegation and example. However, specifically, organizational communication, control functions, and enforcement of disciplinary rules were lacking. This was caused by the weak socialization of vision and mission, organizational structure, task description, and mechanism of inter-departmental relations; the weak supervision of the suitability of the task; and the weak firmness in awarding/sanctioning according to the rules.